UN Ocean Decade Programme AfriMAQUA : network for nutrition-sensitive marine aquaculture in Africa - (:unkn) unknown (My University, 2025)
Aquatic foods?including fish, invertebrates, algae, and aquatic plants?play a crucial role in global food and nutrition security. They provide 15% of global animal proteins and are particularly crucial in many low-income countries. In addition to protein, aquatic foods are rich sources of essential fatty acids, vitamins, and minerals. Despite their importance, these foods are often underrepresented in policy dialogues and funding priorities. Many nations manage aquatic food production predominantly from an economic standpoint, focusing on exports rather than domestic nutritional needs. To shift this paradigm, promoting nutrition-sensitive aquatic food systems is imperative. This involves shifting from viewing fisheries and aquaculture only as a means for producing aquatic foods to a means for promoting overall well-being, requiring the integration of socio-economic, environmental, and cultural dimensions.Over the last thirty years, aquaculture has grown rapidly to meet the increasing global demand of aquatic foods. While per capita consumption of aquatic foods is projected to rise by 2030 globally, Africa is an exception due to population growth outpacing supply. Although African aquaculture production has expanded significantly in recent years, it represents less than 2% of the global aquaculture production, with marine aquaculture production being one of the lowest worldwide.The AfriMAQUA initiative was established in 2019 as a collaborative network of researchers from various African countries and France, aimed at enhancing the sustainability of marine aquaculture in Africa. In 2023, it was endorsed as a programme of the UN Decade of Ocean Science for Sustainable Development 2021-2030. AfriMAQUA seeks to promote South-South-North collaborations and knowledge sharing across Africa, emphasizing coordinated efforts to develop sustainable and nutrition-sensitive marine aquaculture. The programme focuses on 1) fostering collaborative research, 2) enhanci
Keywords: African Research